Relationship between precipitation and rice production in Rangpur district - Rokonuzzaman, M; Rahman, MA; Yeasmin, M; Islam, MA (Progressive Agriculture, 2018)
An experiment was carried out to reveal the precipitation pattern and to find out the interrelationship between precipitation and production of rice in Rangpur district. Rangpur division is more favorable for rice production. Monthly and yearly precipitation data (1983-2013) were collected from Bangladesh Meteorological department (BMD), Agargaon, Dhaka; Bangladesh Agricultural Research Council (BARC), Farmgate, Dhaka and rice production data were collected from Bangladesh Rice research Institute (BRRI); Department of Agricultural Extension (DAE), Rangpur, Bangladesh. From the analyzed precipitation data, it was clearly found that in 1984, 1985, 1987, 1999 and 2005, there were heavy precipitations and resulting flash flood. The average precipitation of Rangpur was higher (1344 mm) in 1987 than 1984, 1985, 1999 and 2005. In Rangpur district, rice production was the highest in the year of 1983, 1986, 1988, 1989, 1990, 1991, 1992, 1993, 1995, 1996, 1997, 1998, 2001, 2002, 2003, 2004, 2007, 2008, 2009, 2010, 2011, 2012 and 2013 and lower in the year of 1984, 1985, 1987, 1994, 1999, 2000, 2005, and 2006 on the basis of total annual precipitation. Rice production reduced main two reasons such as, heavy precipitation causes flash flood and lower precipitation causes drought stress condition. Both are threat-full for higher rice production. The results show that more precipitation in the years of lowest rice production period, heavy precipitation responsible for deduction of rice production area because of flooding and drought and also shows that normal/ minimum precipitation favorable for rice production at Rangpur district. From this study, it is concluded that the irregular precipitation of period (1984, 1985, 1987, 1994, 1999, 2000, 2005, and 2006) was not satisfactory for rice production due to heavy and/or excessive lower precipitation that resulting flood and/or in part of Rangpur district of Bangladesh. The analysis exposed that precipitation was one of the most important factors for higher amount of rice production in Rangpur district. Progressive Agriculture 29 (1): 10-21, 2018